Pengaruh Pemberian Fraksi Ekstrak Etanol Kelopak Bunga Rosella (Hibiscus sabdariffa L.) Terhadap Volume Urin Tikus Putih Jantan - Surya Dharma; Desis Rena; Zet Rizal (Jurnal Farmasi Higea, 2013)
Research on the effect of giving the fraction of ethanolic extracts of roselle calyx  (Hibiscus sabdariffa L.) to male white rats urine volume has been done, the  fraction was given orally at a dose of n-hexane fraction of 95 mg/g BW, the fraction of ethyl acetate 145 mg/g BW and the fraction of the remaining 350 mg/g BW once a days for 7, 14 and 21. Result shows that the fraction of n-hexane giving 95 mg/g BW, fraction ethyl acetate of  145 mg/g BW, and the remaining fraction of 3450 mg/kg BW roselle calyx  (Hibiscus sabdariffa L.) can effect urine volume increased male white rats. Duration of the three fractions on days 7, 14 and 21 show a not significant increase in urine volume (P<0.05).